The Habit of Smoking While Driving: A Phenomenological Study in Balikpapan City - SAPUTRA, Deris Arista (Integration: Journal Of Social Sciences And Culture, 2025)
Purpose:In Balikpapan City, an urban area with industrial activity and high traffic density, this practice represents a complex, risky behavior that cannot be adequately explained solely through legal or health approaches. This qualitative research aims to explore the meanings, experiences, and social processes underlying this phenomenon from the perspective of the perpetrators.Methodology:Using a phenomenological approach combined with case studies, data were collected through in-depth interviews with 15 drivers and participant observation on major roads. The data were analyzed thematically to identify essential patterns in participants' lived experiences.Findings:The research findings reveal three main themes: first, smoking functions as a psychological coping strategy to manage stress and boredom in the temporal pressure of traffic jams; second, this practice is a product of habitus normalized through social learning and peer pressure within the driving community; third, there is a constant inner dialectic between individual enjoyment and awareness of transgression and its social impact.Implication:This study contributes to the enrichment of Bourdieu's habitus theory by introducing the concepts of "mobile habitus" and "dialectical habitus," which are sensitive to the context of mobile spaces and the ambivalence of agents. Practically, these findings highlight the urgency of community-based interventions and socio-cultural approaches in road safety policy, while also opening up space for further research on the transformation of risky habitus in the context of urban mobility.